Distribution of Non-Protein Nitrogenous Extractives in the Muscle of Indian Fish - Mathew, Susheela; M.R., Raghunath; K., Devadasan (Fishery Technology, 2025)
Major non-protein nitrogen (NPN) constituents like trimethyl amine oxide (TMAO), creatine and creatinine, a - amino nitrogen and peptides were estimated in 41 species of marine fish in sea-fresh condition. TMAO was found to be more in elasmobranchs and crustaceans than in teleosts. Euryhaline teleosts entering shallow waters had lower values of TMAO than benthic fish. Creatine and creatinine formed a major portion of NPN in fish, but in crustaceans and squid, only traces of these compounds could be detected, a - Amino nitrogen was found to be more in elasmobranchs and crustaceans. Highest level of peptides was noted in Indian mackerel Rastrelliger kanagurta. Peptide levels were higher in elasmobranchs than in teleosts and lowest in crustaceans.